NEUROLOGICAL MANIFESTATION ON HOSPITALIZED PATIENT WITH PROBABLE COVID-19 IN SAIFUL ANWAR HOSPITAL INDONESIA (SERIAL CASES) - Munir, Badrul; Rianawati, Sri Budhi; Kurniawan, Shahdevi Nandar; Santoso, Widodo Mardi; Arisetijono, Eko; Candradikusuma, Didi; Heri, Sutanto; Chozin, Iin Noor; Dwi, Pratiwi Suryanti; Astuti, Tri Wahju; Asmiragani, Syaifullah (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2020)
Background: Coronavirus disease 2019 (Covid-19) caused by SARS-Cov-2 had been spreading worldwide including Indonesia, but In Indonesia, it was difficult to diagnose confirmation Covid-19 by Polymerase Change Reaction (PCR). and in clinical practice to treat covid-19,Â Indonesia Health Ministry use term probable covid-19 for patients under observation Covid-19, but study for neurological manifestation on Â probable Covid-19 is very lacking.Objective: Knowing the neurological manifestation of patient probable Covid-19.Methods: Observational study from Covid-19 medical record and neuro-Covid-19 medical record of all probable Covid-19 hospitalized in the isolation ward of Saiful Anwar Hospital (RSSA) Malang since March-May, 2020 (3 months). Probable Covid-19 criteria were given by Covid-19 task force team based on Health Minister Indonesia criteria. This criterion was based on clinical manifestation (severe upper respiratory symptoms, or mild-severe pneumonia), radiologic examination (lung infiltrate and or chest CT scan), and laboratory examination. Neurological manifestation is based on clinical symptom appeared while patient hospitalized, supported with radiologic and laboratory data which was supervised by neurologist or neurologist resident. All data was inputted to neuro-Covid-19 e-registry on the smartphone application, sent periodically to the data center in Neurology Department RSSA Malang.Results: A hundred and fourteen probable Covid-19 was registered with mean age 34,5 year old and mostly at the young age of 20-50 years (38%). The neurological manifestation was observed in 4 patients (3,4% from all possible Covid-19 patients) with thrombotic stroke as the most common manifestation (50%), followed by myelum tumor (25%) and hypoxia encephalopathy (25%). Stroke patients in probable Covid-19 had old age (72 and 82 years) accompanied by several comorbid such as hypertension, DM and CVA history and Covid symptoms of cough, shortness of breath and fever. Hemiparesis was found improved with aspirin and neurotropic therapy. Patient with myelum tumor had a covid symptom of shortness of breath, cough, and fever with UMN tetraparesis. Previous MRI examination results suspected meningioma. The patient died while hospitalized. Patients with hypoxia encephalopathy admitted with decreased consciousness due to shortness of breath with acidosis respiratory symptoms (pH 7,22 ). This condition improved after oxygenation without focal neurologic deficit.Conclusion: Neurological manifestation in probable Covid-19 was 3,4% of all patients. The most common diagnosis was a thrombotic stroke, followed by myelum tumor, hypoxia encephalopathy, and mortality rate is 25%.